Seasonal variation in wood formation of Cedrela fissilis (Meliaceae) - Marcati, Carmen Regina [UNESP]; Angyalossy, Veronica; Evert, Ray Franklin (Brill Academic Publishers, 2006)
Cambial activity and periodicity of secondary xylem formation in Cedrela fissilis, a semi-ring-porous species, were studied. Wood samples were collected periodically from 1996 to 2000. The phenology was related to climate data of the region. The cambium has one active and one dormant period per year. The active period coincides with the wet season when trees leaf-out. The dormant period coincides with the dry season when trees lose their leaves. Growth rings are marked by parenchyma bands that begin to be formed, together with the small latewood vessels, just before the cambium becomes dormant at the beginning of the dry season. These bands are added to when the cambium reactivates in the wet season. At this time, the large earlywood vessels of the growth rings are also formed. As these bands consist of both terminal and initial parenchyma, we suggest the general term marginal bands be used to describe them. The growth layers vary in width among and within the trees.
Keywords: Cambial activity; Cedrela fissilis; Marginal parenchyma; Secondary xylem; Xylem differentiation